North Gladiola : A Novel - Wilcox, James (Book collections on Project MUSE., 2000)
Poor Ethyl Mae Coco's life on North Gladiola, in Tula Springs, Louisiana, is really turned upside down when "Gyreen LaSteele, owner of the next-door Tiger Unisex Salon ... accuses Mrs. Coco of killing her beloved chihuahua, Tee-Tee."--Cover